Pengaruh Kualitas Pelayanan Dan Citra Merek Terhadap Kepuasan Pelanggan Pada Laboratorium Klinik Kimia Farma Bengkulu - Zentra Zentra; Ahmad Soleh; Rinto Noviantoro (Universitas Dehasen Bengkulu, 2023)
The purpose of this study was to determine the effect of service quality and brand image on customer satisfaction at the Kimia Farma Bengkulu Clinical Laboratory and researches used research with quantitative descriptive methods. Quantitative research is research that describes and explains phenomena that occur in the field by perfoming statistical calculations.service quality and company brand image are one of the success factors of a company in maintaining customer satisfaction. Cuscomers at Kimia Farma Bengkulu Clinical Laboratory in the results of this study showed that together (simultaneously) revealed service quality and brand image had a very positive and significant effect on customer satisfaction at the Kimia Farma Bengkulu Clinical Laboratory. With this the authors concluded that services quality and brand image plays an important role in customer satisfaction. This is indicated by the probability value (sig) 0.000 <alpha 0.05 including the test criteria Ha is accepted and Ho is rejected.